To find the sum of \( p \) and \( q \), where \( p = \frac{3}{4} \) and \( q = -\frac{11}{4} \), we can perform the following calculation:
\[ p + q = \frac{3}{4} + \left(-\frac{11}{4}\right) \]
This can be simplified as follows:
\[ p + q = \frac{3}{4} - \frac{11}{4} \]
Since the denominators are the same, we can combine the numerators:
\[ p + q = \frac{3 - 11}{4} = \frac{-8}{4} \]
Now, we can simplify \( \frac{-8}{4} \):
\[ \frac{-8}{4} = -2 \]
Thus, the sum \( p + q \) is \(-2\).
To find the sum of \( p \) and \( q \), we can conclude:
\[ p + q = -2 \]
Hence, the answer is:
\[ \boxed{-2} \]